Iron limitation triggers roseoceramide biosynthesis and membrane remodeling in marine roseobacter - Jack G. Ganley; Mohammad R. Seyedsayamdost (Proceedings of the National Academy of Sciences, 2025)
Chemical communication between marine bacteria and their algal hosts drives population dynamics and ultimately determines the fate of major biogeochemical cycles in the ocean. To gain deeper insights into this small molecule exchange, we screened niche-specific metabolites as potential modulators of the secondary metabolome of the roseobacter, Roseovarius tolerans . Metabolomic analysis led to the identification of a group of cryptic lipids that we have termed roseoceramides. The roseoceramides are elicited by iron-binding algal flavonoids, which are produced by macroalgae that Roseovarius species associate with. Investigations into the mechanism of elicitation show that iron limitation in R. tolerans initiates a stress response that results in lowered oxidative phosphorylation, increased import and catabolism of algal exudates, and reconfiguration of lipid synthesis to prioritize production of roseoceramides over phospholipids, likely to fortify membrane integrity as well as promote a sessile and symbiotic lifestyle. Our findings add new small molecule words and their “meanings” to the algal-bacterial lexicon and have implications for the initiation of these interactions.